Animal-Plant Interaction: - Ndizihiwe, Daniel R.; Achille, E Assogbadjo; Sylvestre, C. A. M. Djagoun; Barthélémy KASSA (Exclusive Journal Publishing House, 2018)
The study was based on 107 studies and data concerning disperser species, plant species and family, fruit type and size, seed size plant life form and the habitat, were presented in matrix form. Data from this matrix were used in determining the disperser species diversity considering large taxonomic groups (mammals, birds and reptiles) and selection pattern based on the fruit and seed size. The diversity of mammals was high followed by birds and then reptiles with 65%, 30% and 5% respectively. Mammal taxonomic group dominated and was sub divided into primates, ungulates, carnivores, rodents and bat sub-groups which accounted for 45%, 22%, 17%, 9% and 7% respectively confirming the dominance of primates. Simple correspondence analysis showed that ungulates dispersed very small fruits while carnivores, primates, bats and reptiles were categorized together for both small and medium sized fruits. Ungulates, birds and bats dispersed the smallest seeds while others dispersed both small and large sized seeds. The study revealed high diversity of mammals particularly primates therefore playing a huge role in structuring and restructuring terrestrial ecosystems, with a warning that the loss of ungulates may have catastrophic impacts on the structure and composition of small fruited and seeded plants.